Impact of oil price on economic growth, real effective exchange rate and inflation in South Africa, Morocco and Cote D' Ivoire - Saidu, Mohammad Tukur (2021)
The research study aims to investigates the impact of oil price dynamics on Economic Growth, Real Effective Exchange Rate and CPI net oil importing Countries of South Africa, Morocco and Cote d'Ivoire. Using linear and Nonlinear Autoregressive Distributed Lag (ARDL and NARDL) bound testing framework. It shows that the variables are cointegrated of both order I (0) and I (l) which makes it deem applicable to employ autoregressive model that allowed for the combination of different order. Short run and long run nonlinearities are employed by partial sum decomposition to obtains positive and negative partial sum of oil price using a quarterly data over the period between l983Q2 to 2020Q4 in the present of Structural. Same techniques are applied for all the objectives. Findings from South Africa and Morocco indicates higher oil price leads to a decline in real GDP. Whereas lower oil price leads to an increase in real GDP with asymmetric and symmetric effect, while insignificant in Cote d'Ivoire. However, lower oil price is insignificant. This is because the price increase is absorbs through subsidy provision by government and at the same time Cote d'Ivoire is crude oil exporter, which mean higher oil price increases oil revenue earning from crude oil export. In the second objective, oil price increase leads to currency depreciation in South Africa (Rand) and Cote d'ivoire francs (XOF) in the long and short run. While an appreciation of Dirham (Dirham) for both NARDL and ARDL. Whereas, lower oil price shows appreciation of Rand (ZAR) and francs (XOF), with insignificant in Morocco having a long run symmetry ated to a higher CPI in South Africa and Morocco, but insignificant in NARDL. Similarly, lower oil price led to a positive increase in CPI. This explains a situation of increase in economic activities couples with increased consumption of oil leading to higher CPI. In Cote d'Ivoire higher oil price leads to a decline in CPI due to earning from crude oil sales which could triggered increase in economic output upsetting effect of price increase. Moreover, lower oil price cause an increase in CPI in the long run with a long run symmetry. The government should implement policies in stabilizing prices and measures to curve CPI stemming from oil price increase associated with currency depreciation. This would approach to keep price within a stable limit and removal of energy subsidy to allows the pass-through to consumer.